2005
DOI: 10.1111/j.1365-2958.2004.04470.x
|View full text |Cite
|
Sign up to set email alerts
|

pfmdr1 mutations associated with chloroquine resistance incur a fitness cost in Plasmodium falciparum

Abstract: SummaryEfforts to control malaria worldwide have been hindered by the development and expansion of parasite populations resistant to many first-line antimalarial compounds. Two of the best-characterized determinants of drug resistance in the human malaria parasite Plasmodium falciparum are pfmdr1 and pfcrt , although the mechanisms by which resistance is mediated by these genes is still not clear. In order to determine whether mutations in pfmdr1 associated with chloroquine resistance affect the capacity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 76 publications
8
68
0
Order By: Relevance
“…In this study, we investigated both of these mechanisms and found that each contributed to the observed instability. The loss of fitness observed can be attributed to the amplification of a large section on chromosome 5 and changes in the pfmdr1 CN, not additional mutations in pfmdr1, as previously reported (11), or in several resistance gene candidates, such as pfatp6, since no additional mutations were identified in the resistant progeny (6). Importantly, our study used cloned parasites, allowing us to distinguish deamplification of pfmdr1 from out-growth by a preexisting subpopulation of parasites with a low CN.…”
Section: Discussionmentioning
confidence: 52%
“…In this study, we investigated both of these mechanisms and found that each contributed to the observed instability. The loss of fitness observed can be attributed to the amplification of a large section on chromosome 5 and changes in the pfmdr1 CN, not additional mutations in pfmdr1, as previously reported (11), or in several resistance gene candidates, such as pfatp6, since no additional mutations were identified in the resistant progeny (6). Importantly, our study used cloned parasites, allowing us to distinguish deamplification of pfmdr1 from out-growth by a preexisting subpopulation of parasites with a low CN.…”
Section: Discussionmentioning
confidence: 52%
“…Other studies have documented cases where drug resistanceassociated mutations confer a fitness disadvantage in the absence of drug pressure (20,21), but this does not seem to be the case with Pfmspdbl2. This could be due to the modest change in drug response conferred by the C591S mutation or perhaps because compensatory mutations that restore parasite fitness have occurred.…”
Section: Discussionmentioning
confidence: 97%
“…In a recent study, Hayward et al (2005) proposed that growth rate differences in genetically modified parasites result from a fitness impact of mutations introduced in pfmdr1. Using merozoite number as a growth criteria they ruled out differential merozoite production as contributing to growth differences in these lines.…”
Section: Discussionmentioning
confidence: 99%